2004
DOI: 10.1136/bjo.2003.037887
|View full text |Cite
|
Sign up to set email alerts
|

The effect of corneal thickness on intraocular pressure measurement in patients with corneal pathology

Abstract: Background/aim: To compare intraocular pressure (IOP) measurements taken by the Goldmann applanation tonometer, the Tono-Pen and the ocular blood flow pneumotonometer in eyes with varying central corneal thickness (CCT) due to penetrating keratoplasty (PK), keratoconus (KC), and Fuchs' endothelial dystrophy (FED). Methods: IOP was measured with the Goldmann applanation tonometer, Tono-Pen XL, and OBF pneumotonometer in 127 eyes with the following corneal abnormalities. There were 56 eyes that had undergone PK,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 36 publications
(32 reference statements)
2
37
0
1
Order By: Relevance
“…CCT measurement revealed that P2Y 6 KO mice showed thicker CCT at middle age. Many reports have suggested that IOP is positively correlated to CCT (67)(68)(69)(70)(71)(72)(73)(74)(75). Our present data demonstrated that mature adult P2Y 6 KO Figure 6.…”
Section: Discussionsupporting
confidence: 73%
“…CCT measurement revealed that P2Y 6 KO mice showed thicker CCT at middle age. Many reports have suggested that IOP is positively correlated to CCT (67)(68)(69)(70)(71)(72)(73)(74)(75). Our present data demonstrated that mature adult P2Y 6 KO Figure 6.…”
Section: Discussionsupporting
confidence: 73%
“…In the present study, considering the relatively small thickness of the porcine cornea to the spatial resolution of the SS-OCT system, 24 3 -voxel sub-volumes with 50% overlap were used to perform DVC. This sub-volume size can enhance the strain spatial resolution; nevertheless, it increases strain noise level, as proposed in [45], where the noise level increases from around when the sub-volume size reduces from 36 3 to 24 3 .…”
Section: Resultsmentioning
confidence: 99%
“…Its structural integrity, shape and transparency are essential to maintain optical performance. Abnormalities in its composition or structure due to disorders or disease such as keratoconus, corneal dystrophy, glaucoma or mass lesions, to name a few, severely degrade vision [3][4][5][6][7]. Ablative laser surgery is widely used to correct refractive performance and improve visual acuity, with more than one million operations in the United States alone each year [8].…”
Section: Introductionmentioning
confidence: 99%
“…Para uso clínico, a leitura mais alta da PIO no TCDP deve ser considerada. Entretanto, as medidas como TCDP parecem não depender da ECC, corroborando alguns trabalhos (2)(3)(4)11,(13)(14) . Brusini e cols.…”
Section: Discussionunclassified